2007
DOI: 10.1063/1.2819613
|View full text |Cite
|
Sign up to set email alerts
|

Phase structure of epitaxial Pb(Zr,Ti)O3 thin films on Nb-doped SrTiO3 substrates

Abstract: Epitaxial Pb(Zr,Ti)O3 (PZT) films were deposited on Nb-doped SrTiO3 (Nb:STO) monocrystalline wafers by a sol-gel method. It was observed that phase structure of prepared films depends on the orientation of Nb:STO substrates. Interestingly, tetragonal structure was only found for [001]-oriented PZT film on Nb:STO(100) substrate, whereas Nb:STO(111) substrate resulted in a [111]-oriented rhombohedral PZT film, regardless of Zr∕Ti ratios ranging from 40∕60 to 60∕40. The influence of substrate orientation on phase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 26 publications
3
26
1
Order By: Relevance
“…However, it is difficult to fabricate epitaxial PZT thin films with an MPB phase structure which may be caused by biaxial compressive stress in epitaxial films resulting in changes in the phase structure, as suggested by Oh et al [9]. The prediction is consistent with our previous study [13,14] where we found that epitaxial PZT thin films could be formed on Nb-doped SrTiO 3 substrates by a sol-gel process. Their phase structures can be substantially affected by the substrate orientations due to the mechanical constraints, motivating us to systematically investigate the compositional dependence of the phase structure and electromechanical properties of epitaxial PZT thin films in a broad compositional range using combined experimental and theoretical approaches as are shown in this report.…”
Section: Introductionsupporting
confidence: 90%
See 2 more Smart Citations
“…However, it is difficult to fabricate epitaxial PZT thin films with an MPB phase structure which may be caused by biaxial compressive stress in epitaxial films resulting in changes in the phase structure, as suggested by Oh et al [9]. The prediction is consistent with our previous study [13,14] where we found that epitaxial PZT thin films could be formed on Nb-doped SrTiO 3 substrates by a sol-gel process. Their phase structures can be substantially affected by the substrate orientations due to the mechanical constraints, motivating us to systematically investigate the compositional dependence of the phase structure and electromechanical properties of epitaxial PZT thin films in a broad compositional range using combined experimental and theoretical approaches as are shown in this report.…”
Section: Introductionsupporting
confidence: 90%
“…The observed fourfold symmetry (not shown) clearly indicates a well epitaxial relationship between the deposited PNZT films with different Zr/Ti ratios and the Nb:STO(1 0 0) substrates. This result is consistent with our previous work [14]. In order to examine a possible phase transition when the Zr/Ti ratio is changed, the (0 0 4)-reflections of films are precisely step-scanned (Fig.…”
Section: Phase Structure Characterizationsupporting
confidence: 78%
See 1 more Smart Citation
“…In the range of 2θ from 18° to 52°, only two peaks -namely, the (001) and (002) reflections -corresponding to the perovskite PZT phase can be observed. 55 In addition, HRXRD indicates the epitaxial growth of single-phase, fully strained LSMO(00l) with lattice parameter c = 3.85 Å on (001)-oriented STO:Nb; more details are given elsewhere. 43 To better characterize the crystallinity of the mesoporous PZT with regard to texture and uniformity, both a φ scan, by tilting to 44.56°, on the (110) reflection and an ω scan (rocking curve measurement) on the (001) reflection at 2θ = 21.84° were conducted.…”
Section: Resultsmentioning
confidence: 99%
“…Many of these properties are maximized near the morphotropic phase boundary (MPB) with a Ti composition of 0.48 [3][4][5][6]. Moreover, orientation engineering is a suitable approach to improve the physical properties of the PbðZr 1 À x Ti x ÞO 3 thin films [7][8][9][10]. Therefore, control of the composition and film orientation can be used to modulate the physical properties of the ferroelectric thin films.…”
Section: Introductionmentioning
confidence: 98%